Chemistry experiments as a differentiator to improve teaching-learning - Pereira, Maira Mendes; Montanher, Silvana Fernandes; Lira, Helvia Nancy Fuzer; Ströher, Gylles Ricardo; Ströher, Gisely Luzia (Seven Editora, 2024)
This work was developed with underprivileged girls between 10 and 15 years of age enrolled in public schools in the city of Apucarana, State of Paraná, Brazil, hosted by NGOs. The proposal involved improving the participants’ learning in mathematics, physics and chemistry. To gain the interest of this audience, the project carried out scientific experiments such as: chemical chameleon, atmospheric pressure, balloon, lemon stack and pH with cabbage. These experimental practices were involved in explanations and resolutions of exercises involving everyday life. The main doubts involved mathematics that were carried over to chemistry and/or physics exercises. Resolving difficulties in mathematics proved to be a differentiator in boosting interest in other areas, such as chemistry and physics. Among the experiments carried out, it was observed that the chemical chameleon and the pH with cabbage were better evaluated by the participants. The scientific experiments carried out helped to bring university students closer to underprivileged girls in the local community. However, the work promoted opportunities for academics to apply theoretical knowledge and develop and improve themselves as professionals. DOI:https://doi.org/10.56238/sevened2023.008-029